Delivery of Basic Fibroblast Growth Factor Through an In Situ Forming Smart Hydrogel Activates Autophagy in Schwann Cells and Improves Facial Nerves Generation via the PAK-1 Signaling Pathway - Hu, Binbin; Zhang, Hanbo; Xu, Menglu; Li, Lei; Wu, Man; Zhang, Susu; Liu, Xuejun; Xia, Weidong; Xu, Ke; Xiao, Jian; Zhang, Hongyu; Ni, Liyan (Frontiers in Pharmacology, 2022)
Although studies have shown that basic fibroblast growth factor (bFGF) can activate autophagy and promote peripheral nerve repair, the role and the molecular mechanism of action of bFGF in the facial nerve are not clear. In this study, a thermosensitive in situ forming poloxamer hydrogel was used as a vehicle to deliver bFGF for treating facial nerve injury (FNI) in the rat model. Using H&E and Masson's staining, we found that bFGF hydrogel can promote the functional recovery and regeneration of the facial nerve. Furthermore, studies on the mechanism showed that bFGF can promote FNI recovery by promoting autophagy and inhibiting apoptosis. Additionally, this study demonstrated that the role of hydrogel binding bFGF in nerve repair was mediated through the activation of the PAK1 signaling pathway in Schwann cells (SCs). These results indicated that poloxamer thermosensitive hydrogel loaded with bFGF can significantly restore the morphology and function of the injured facial nerve by promoting autophagy and inhibiting apoptosis by activating the PAK1 pathway, which can provide a promising strategy for FNI recovery.